Comparing the accuracy of four electronic apex locators for determining the minor diameter: An ex vivo study - KARTAL, NEVİN; CİMİLLİ, ZÜHRE HALE (ELSEVIER TAIWAN, 2013)
Background/purpose: The purpose of this study was to assess the accuracy of the minor apical diameter, as measured by the Root ZX II, Raypex 5, Propex, and ATR EndoPlus electronic apex locators (EALs). Materials and methods: We selected 40 extracted maxillary incisors and used the locator instruments to measure the distance from the coronat reference point to the file tip at the major diameter. We termed this the reference canal length (RCL). Files were stabilized in position with a flowable composite. We then shaved 4 mm from the apical region and took photographs of the canal termination at 64% magnification to visualize the minor diameter. The minor diameter length (MDL) was then calculated. Results: Measurements with Raypex 5 (15.22 +/- 1.79 mm), Root ZX 11 (15.24 +/- 1.73 mm), Propex (15.22 +/- 1.76 mm) and ATR EndoPlus (15.27 +/- 1.78 mm) were significantly smaller than the MDL (15.43 +/- 1.75 mm) (P < 0.05). When measurements were evaluated to within +/- 0.5 mm, the MDL determination was 82.5% acceptable for the Root ZX II and the ATR EndoPlus, and was 85% acceptable for the Raypex 5 and the Propex. Conclusion: The accuracy of these instruments for detecting the minor diameter is acceptable for clinical practice. Copyright (c) 2012, Association for Dental Sciences of the Republic of China. Published by Elsevier Taiwan LLC. All rights reserved.
Keywords: apex locator; major foramen; minor constriction; WORKING LENGTH DETERMINATION; ELEMENTS DIAGNOSTIC UNIT; ROOT-ZX; IN-VITRO; CANAL INSTRUMENTATION; PRECISION; FORAMEN; ABILITY; PROPEX